Influência da incontinência urinária na qualidade de vida de idosos - Santos, Michely de Oliveira (2018)
Introduction: With the population advancing the reduction of the birth rate and mortality, the population becomes more aged, increasing the life expectancy, number of diseases and changes common to the elderly. Among these, urinary incontinence (UI), generating impact on the quality of life (QoL) of the elderly. Objective: To evaluate the influence of UI on QoL. Materials: This is an exploratory and descriptive cross-sectional study, carried out with a sample of 21 elderly individuals aged 60 years or older. Data were collected through the King's Health Questionnaire (KHQ) questionnaire to assess the quality of life of the elderly with UI and the Mini Mental State Examination (MMSE) to assess cognitive ability. After data collection, the data was organized into a table in the Microsoft Office Excel program. Results: According to data from the KHQ questionnaire, there was a predominance of elderly people who assessed their health as good and with little impact of UI on QoL. With regard to UI symptoms, most reported moderate UI of urgency, stress UI, nocturia, and overactive bladder; few frequent infections, nocturnal enuresis and bladder pain; and, absence of sexual intercourse incontinence and other bladder problems. Conclusion: The score of the scores in the domains evaluated showed that the UI had little influence on the QoL of the elderly. However, the obtained results present subsidies for the planning of specific interventions for the sample, in order to prevent worsening of the symptoms and the quality of life of the elderly.